IMPLEMENTATION OF DIGITAL-BASED HUMAN RESOURCE MANAGEMENT IN GOVERNMENT AGENCIES IN BANDUNG CITY - Ade Mubarok (CV. Radja Publika, 2022)
The implementation of digital-based human resource management (HRM) has become an important strategy in improving the effectiveness and efficiency of public sector organizations. This study aims to analyze the implementation of digital HRM systems in government agencies in Bandung City, focusing on their benefits, challenges, and contributions to organizational performance. The research used a qualitative descriptive method with data collection techniques including interviews, observations, and documentation. The findings indicate that digital HRM systems have improved administrative efficiency, transparency, employee performance monitoring, and accessibility of personnel information. The use of digital systems also supports faster decision-making processes and enhances accountability within government institutions. However, several challenges remain, including limited employee digital competencies, inadequate technological infrastructure, system integration issues, and concerns regarding data security. The study concludes that digital-based HRM has significant potential to support bureaucratic reform and improve public service quality in Bandung City government agencies. Continuous training, infrastructure improvement, and organizational commitment are necessary to maximize the effectiveness of digital transformation in the public sector.